FOXP3+ regulatory T cells and the immune escape in solid tumours - Qiu, Yiran; Ke, Shouyu; Chen, Jieqiong; Qin, Zhizhen; Zhang, Wenle; Yuan, Yaqin; Meng, Dehua; Zhao, Gang; Wu, Kejin; Li, Bin; Li, Dan (Frontiers in Immunology, 2022)
FOXP3+ regulatory T (Treg) cells play critical roles in establishing the immunosuppressive tumour microenvironment, which are achieved and dynamically maintained with the contribution of various stromal and immune cell subsets. How non-lymphoid FOXP3+Treg cells dynamics and other cells in solid tumour microenvironment mutually regulate each other remains largely unclear. In this review article, we summarize the latest findings on the dynamic connection and reciprocal regulation of non-lymphoid Treg cell subsets with both well-established and new emerging hallmarks of cancer, especially on the immune escape in solid tumours. Our understanding on the mutual regulation of FOXP3+Treg cells and key hallmarks of cancer may provide new clues on designing next-generation engineered T cell-based immune therapies for treating solid tumours.